PENGARUH CYBER CRIME DAN PERCEIVED RISK TERHADAP PENGAMBILAN KEPUTUSAN MENGGUNAKAN E-BANKING BANK SYARIAH INDONESIA (BSI) - Rulinda Aini; Zainul Hasan Quthbi; Hadratullah Hadratullah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the influence of cyber crime and perceived risk on decision-making in using e-banking services at Bank Syariah Indonesia (BSI). The background of this research is the increasing use of digital banking services, which is accompanied by potential threats of cybercrime and users’ perceived risks. This research employed a quantitative approach with an associative descriptive method. The sample consisted of 96 respondents, determined using Slovin’s formula, with data collected through questionnaires. Validity and reliability tests confirmed that all research instruments were valid and reliable. The data were analyzed using classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination with the help of SPSS version 25. The findings revealed that the cyber crime variable has a negative but insignificant effect on students’ decision to use BSI e-banking services. This indicates that although cybercrime remains a relevant issue, it does not significantly reduce users’ intention to adopt digital banking. On the other hand, the perceived risk variable shows a positive and significant effect on decision-making. The better students perceive and manage risks, the higher their tendency to use BSI e-banking services. Simultaneously, both variables significantly influence decision-making, with perceived risk contributing more strongly than cyber crime. These results highlight that a well-managed perception of risk can enhance users’ confidence in adopting Islamic digital banking services.